PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN LKS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI JENIS USAHA DAN KEGIATAN EKONOMI DI KELAS V SDN 12 CAKRANEGARA - Nisa, Khairun; Istiningsih, Siti; Novitasari, Setiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the influence of the LKS-assisted Problem Based Learning learning model on students' critical thinking skills on the type of business material and economic activities in grade V SDN 12 Cakranegara. This type of research is quantitative research using Pre-Experimental. The research design used was One Group Pretest-Posttest Design. The number of subjects in this study was 22 students. Data collection techniques used observation and tests. Observation is used to see the implementation of the Problem Based Learning learning model and tests are used to measure students' critical thinking skills. In this study the prerequisite test consisted of a normality test using Shapiro Wilk, and a hypothesis test using the Polled Variance t-test. The results of the study obtained from the hypothesis test are significant values (2tailed) 0.000 which means 0.000 < 0.05, then H0 is rejected and Ha is accepted. This shows that there is an influence of the LKS-assisted Problem Based Learning learning model on students' critical thinking skills on the type of business material and economic activities in grade V SDN 12 Cakranegara.